2019
DOI: 10.1097/coc.0000000000000573
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Toxicity in Operable Esophageal Cancer Patients Treated With or Without Chemoradiation

Abstract: Purpose: To evaluate predictors of cardiac events in esophageal cancer patients treated with neoadjuvant chemoradiotherapy followed by surgery (NA CRT) compared with surgery alone. Methods and materials: We retrospectively identified patients treated for esophageal cancer between 2006 and 2016. 123 patients were identified; 70 were treated with surgery alone, and 53 were treated with NA CRT. Cardiac events were scored based on Common Terminology Criteria for Adverse Events (CTCAE v4.03), and dosimetric data wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 18 publications
1
12
0
Order By: Relevance
“…Thoracic radiotherapy is an important cancer treatment for patients diagnosed with malignant tumors, such as breast cancer, lung cancer, Hodgkin's lymphoma and esophageal cancer (1)(2)(3)(4). radiotherapy improves overall survival (oS) in patients with thoracic cancer, but it can result in some inevitable complications, particularly radiation-induced heart damage (riHd), which has gradually become an increasing concern of oncologists and cardiologists (5,6).…”
Section: Introductionmentioning
confidence: 99%
“…Thoracic radiotherapy is an important cancer treatment for patients diagnosed with malignant tumors, such as breast cancer, lung cancer, Hodgkin's lymphoma and esophageal cancer (1)(2)(3)(4). radiotherapy improves overall survival (oS) in patients with thoracic cancer, but it can result in some inevitable complications, particularly radiation-induced heart damage (riHd), which has gradually become an increasing concern of oncologists and cardiologists (5,6).…”
Section: Introductionmentioning
confidence: 99%
“…A series of single institution studies with sample sizes ranging from 15 to 123 have described a similar association between radiation in esophageal cancer and a variety of cardiovascular endpoints. This includes studies identifying a link between radiation and increased myocardial perfusion defects 7 , decreased ejection fraction 8,9 , and clinically significant cardiac toxicity 10,11 . Similarly, a study evaluating patients within SEER found a 2.8% absolute increased risk of death from cardiovascular disease among esophageal cancer patients treated with radiation 12 .…”
Section: Discussionmentioning
confidence: 99%
“…With other cancer types, including breast cancer, lung cancer, and Hodgkin's lymphoma, large clinical studies demonstrate a clear link between thoracic radiation and adverse cardiovascular outcomes [4][5][6] . Multiple small institutional studies have demonstrated a potential link between radiation and cardiovascular disease in esophageal cancer patients treated with radiotherapy [7][8][9][10][11] . Additionally, a study evaluating patients within the Surveillance Epidemiology and End Results (SEER) cancer registry found increased cardiovascular mortality among esophageal cancer patients receiving radiation 12 .…”
Section: Introductionmentioning
confidence: 99%
“…In patients undergoing CRT for esophageal cancer, up to 10.8% develop symptomatic cardiac toxicity (44). Institutional retrospective and database analyses show that compared to patients who undergo esophagectomy alone, those who undergo nCRT have a significantly increased risk of grade 3 or higher cardiac events and that higher radiation doses to the heart correlates with a higher incidence of cardiac events (45)(46)(47). In a prospective phase II trial by Lin et al, 145 patients with esophageal cancer were randomized to definitive treatment with proton beam therapy or photon-based intensity-modulated radiation therapy.…”
Section: Reducing Treatment-related Toxicitymentioning
confidence: 99%